2013
DOI: 10.1371/journal.pone.0067003
|View full text |Cite
|
Sign up to set email alerts
|

SLE Peripheral Blood B Cell, T Cell and Myeloid Cell Transcriptomes Display Unique Profiles and Each Subset Contributes to the Interferon Signature

Abstract: Systemic lupus erythematosus (SLE) is a chronic autoimmune disease that is characterized by defective immune tolerance combined with immune cell hyperactivity resulting in the production of pathogenic autoantibodies. Previous gene expression studies employing whole blood or peripheral blood mononuclear cells (PBMC) have demonstrated that a majority of patients with active disease have increased expression of type I interferon (IFN) inducible transcripts known as the IFN signature. The goal of the current study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
129
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(146 citation statements)
references
References 77 publications
16
129
1
Order By: Relevance
“…It was shown that B cells display a significant IFN-I inducible gene signature in SLE patients [19]. Consistently, we also observed higher IFIT1, IFIT2, MX1, OAS1, USP18, and IFI44 expression levels, which are downstream genes of the JAK1-STAT1 signaling cascade (Supporting Information Fig.…”
Section: Sts-1 Promotes Ifn-α-induced Autophagy Through Jak1-stat1 Sisupporting
confidence: 88%
See 1 more Smart Citation
“…It was shown that B cells display a significant IFN-I inducible gene signature in SLE patients [19]. Consistently, we also observed higher IFIT1, IFIT2, MX1, OAS1, USP18, and IFI44 expression levels, which are downstream genes of the JAK1-STAT1 signaling cascade (Supporting Information Fig.…”
Section: Sts-1 Promotes Ifn-α-induced Autophagy Through Jak1-stat1 Sisupporting
confidence: 88%
“…As is known, the TLR7, TLR9, BCR, and IFN-α pathways are aberrantly activated in SLE B cells [19,30,31]. To identify the molecular events leading to STS-1 overexpression, we evaluated the effects of the TLR7, TLR9, BCR, and IFN-α pathways on STS-1 expression regulation in B cells.…”
Section: The Tlr7 Tlr9 and Bcr Pathways Upregulate Sts-1 Expressionmentioning
confidence: 99%
“…Several gene expression studies have contributed to the discovery of genes related to SLE, especially those studies focused on gene transcripts in T cells and B cells. 33,40,41 In this study, we found that most DEGs were enriched in cell cycle pathways in SLE B cells. In accordance with our analysis, the publicly available datasets for the SLE transcriptome also revealed that significant pathways of overexpressed genes are related to the cell cycle.…”
Section: Discussionmentioning
confidence: 53%
“…It will be interesting to investigate whether other chronic innate immune activation mouse models present similar metabolic phenotypes. Nonetheless, because metabolic dysregulation is becoming more commonly observed in autoimmune diseases such as SLE, which is often associated with elevated type I IFN gene signature and chronic activation of TBK1-dependent innate immune pathways (21,25,26). The molecular mechanism we delineated here with the Trex1 −/− mouse model highlight TBK1 as a potentially useful therapeutic target that mediates the crosstalk between immune response and metabolism.…”
Section: Chronic Inflammation Dysregulated Metabolismmentioning
confidence: 83%